A novel polymer donor based on dithieno[2, 3-d:2′, 3′-d′′]benzo[1, 2-b:4, 5-b′]dithiophene for highly efficient polymer solar cells. Issue 6 (18th January 2019) - Huang, Jiaming; Peng, Ruixiang; Xie, Lingchao; Song, Wei; Hong, Ling; Chen, Sanhui; Wei, Qiang; Ge, Ziyi
Abstract : A novel polymer was used as the donor material in organic solar cells to achieve the best photovoltaic performance based on DTBDT. Abstract : A novel polymer material, poly{5, 10-bis(5-ethylhexyl-4-fluorothiophen-2-yl)dithieno[2, 3- d :2′, 3′- d ′′]benzo[1, 2- b :4, 5- b ′]dithiophene- co -1, 3-bis(thiophen-2-yl)-5, 7-bis(2-ethylhexyl)-4 H, 8 H -benzo[1, 2- c :4, 5- c ′]dithiophene-4, 8-dione} (PDBT-F) is designed, synthesized, and used as a donor in polymer solar cells. Dithieno[2, 3- d :2′, 3′- d ′′]benzo[1, 2- b :4, 5- b ′]dithiophene (DTBDT) with an extended conjugation length shows better π–π stacking, higher charge-carrier mobility, and broader absorptions to boost the photovoltaic performance. Further introducing fluorine atoms in side groups effectively deepens the highest occupied molecular orbital (HOMO) level to enhance the open-circuit voltage ( V oc ), promotes π–π stacking to increase the short-circuit current density ( J sc ), thus obtaining a power conversion efficiency (PCE) of 11.02% with IDIC. Moreover, ternary devices of PDBT-F:IDIC:PC71 BM are constructed. As expected, the ternary device shows a higher J sc by virtue of the absorption complementarity of PDBT-F:IDIC:PC71 BM, thus gaining extended absorption; a higher V oc is caused by the deep lowest unoccupied molecular orbital (LUMO) level of PC71 BM. The cascaded LUMO levels of PDBT-F, PC71 BM and IDIC facilitate the charge transfer, finally achieving a PCE of 11.86% with a PC71 BM content of 10%. The results we report show the best performances based on DTBDT materials. This work also demonstrates that it is a wise strategy to combine a fullerene derivative with non-fullerene acceptors to construct high-performance ternary solar cells.